Potential Acetaminophen and Opioid Overdoses in Young Children Prescribed Combination Acetaminophen/Opioid Preparations. Issue 2 (November 2016) - Basco, William T.; Garner, Sandra S.; Ebeling, Myla; Hulsey, Thomas C.; Simpson, Kit
Abstract : Introduction: Combination preparations of acetaminophen/opioid are the most common opioid form prescribed to children. We tested the hypothesis that dispensed prescriptions of acetaminophen/opioid preparations more appropriately match acetaminophen dosing parameters than opioid dosing parameters. We also hypothesized that the frequency of potential overdose was inversely related to subject age. Methods: Using 2011 to 2012 South Carolina outpatient Medicaid data, the authors identified acetaminophen/opioid preparations dispensed to children 0 to 36 months. Utilizing Centers for Disease Control and Prevention (CDC) data to impute subject weights as the 97th percentile for age and gender, the authors used imputed weights to calculate the maximum recommended daily dose (expected dose) of each component. We calculated the dose delivered per day (observed dose) based on drug concentration, volume dispensed, and days' supply and then calculated the frequency of overdose (observed dose/expected dose, >1.10) by each component, comparing overdose frequency of acetaminophen to the overdose frequency of opioid using a risk ratio. Logistic regression evaluated differences in potential overdose by age, controlling for race/ethnicity and gender. Results: Among 2, 653 dispensed prescriptions of study drugs to 2, 308 children 0 to 36 months old, the frequency of potential overdose was 0.7% for acetaminophen and 1.6% for opioid (risk ratio, 2.28). Age less than 3 months was associated with a greater frequency of potential overdose of either acetaminophen or opioid, even after controlling for gender and race/ethnicity. Conclusions: Prescriptions of acetaminophen–opioid drugs dispensed to children 0 to 36 months old contained potential overdoses of opioid at greater than twice the frequency of acetaminophen and were more likely to occur in infants less than 3 months old.